A standard of care for individuals with PIK3CA‐related disorders: An international expert consensus statement. Issue 1 (16th July 2021) - Douzgou, Sofia; Rawson, Myfanwy; Baselga, Eulalia; Danielpour, Moise; Faivre, Laurence; Kashanian, Alon; Keppler‐Noreuil, Kim M.; Kuentz, Paul; Mancini, Grazia M. S.; Maniere, Marie‐Cecile; Martinez‐Glez, Victor; Parker, Victoria E.; et al.
Abstract: Growth promoting variants in PIK3CA cause a spectrum of developmental disorders, depending on the developmental timing of the mutation and tissues involved. These phenotypically heterogeneous entities have been grouped as PIK3CA ‐Related Overgrowth Spectrum disorders (PROS). Deep sequencing technologies have facilitated detection of low‐level mosaic, often necessitating testing of tissues other than blood. Since clinical management practices vary considerably among healthcare professionals and services across different countries, a consensus on management guidelines is needed. Clinical heterogeneity within this spectrum leads to challenges in establishing management recommendations, which must be based on patient‐specific considerations. Moreover, as most of these conditions are rare, affected families may lack access to the medical expertise that is needed to help address the multi‐system and often complex medical issues seen with PROS. In March 2019, macrocephaly‐capillary malformation (M‐CM) patient organizations hosted an expert meeting in Manchester, United Kingdom, to help address these challenges with regards to M‐CM syndrome. We have expanded the scope of this project to cover PROS and developed this consensus statement on the preferred approach for managing affected individuals based on our current knowledge. Abstract : XXX.